Implementasi Kebijakan Mitigasi Dan Kesiapsigaan Bencana Pada Badan Penanggulangan Bencana Daerah Kabupaten Bima - Mas’ud Mas’ud; Haeril Haeril (Serat Acitya, 2022)
The aim of this research is to determine the implementation of mitigation and preparedness policies regarding disaster management in the Bima Regency area. This study used descriptive qualitative method. The location of this research is at the Regional Disaster Management Agency (BPBD) Bima Regency Office. Data collection techniques consist of observation, interviews and documentation. The research results show that regional capacity level data in disaster management shows that aspects of community preparedness through PODES data and in-depth interviews with office holders at the sub-district level are still very weak. That due to the weak regional capacity index in efforts to reduce disaster risk, the level of preparedness for various types of disasters in the community is also low, automatically the level of risk that will occur in the community is very vulnerable. Community preparedness policies have not yet become a priority activity. However, in strengthening preparedness, the Regional Government of Bima Regency has implemented institutional technical capacity policies as well as strong disaster emergency management mechanisms with a disaster risk reduction perspective. The Bima Regency Government is also exploring ready disaster contingency plans at all levels of Government, holding regular exercises to test and develop disaster emergency response programs. And most importantly, the Regional Government must provide financial and logistical reserves as well as anticipatory mechanisms that are ready to support effective disaster management efforts. One of the efforts of the Bima Regency Regional Government is to determine priority disasters. Determining priority disasters in Bima Regency using a priority disaster matrix based on data on disaster risk levels and data on trends in disaster occurrence for each type of disaster.